Pre season VO2max estimation of young male elite basketball players - Sempf, F.; Brahms, C. M.; Thienes, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Aerobic capacity is an important determinant of team sport performance that can accurately be assessed with spirometry. Due to the complex set up and high costs, there is a need to establish quick and feasible alternatives. One popular field test is the shuttle run, which has repeatedly been shown to yield accurate and valid VO2max estimates (Mayorga-Vega et al., 2015). Additionally, modern heart rate monitors (HRM) have been equipped with complex algorithms that allow aerobic capacity to be measured at rest. However, the accuracy of HRM methods has not yet been investigated for young team sport athletes. Consequently, the purpose of this study was to compare two different field-test estimates of aerobic capacity in a group of young elite basketball players. Methods 10 male elite basketball players (height = 188,3cm ± 6,5; weight = 79,51kg ± 9,4; age = 17,1 ± 0,86) were recruited for this study. Participants were equipped with a chest-strap and an associated HRM (Polar M400). The activity level was selected based on the current training status (5-8 hours/ week) and anthropometric data entered into the HRM. The participants laid down and rested for approximately 5 minutes. After this time, the HRM automatically provided an estimate of the aerobic capacity. Next, the participants performed an all-out shuttle run test to reassess aerobic capacity. Results The average VO2max value estimated by the HRM method was 55.3 (+/- 3.9) ml/kg/min, compared to 53.4 (+/- 3.9) ml/kg/min in the shuttle run. Paired-samples t-test did not reveal any significant differences between VO2max methods (p = 0.276). Discussion The results indicate that the estimates of aerobic capacity provided by the HRM are similar to those established by the fatiguing shuttle-run test. Although, true VO2max was not assessed in this experiment, the HRM method was compared to a reliable and valid field test. Previous research has found different correlation coefficients between the HRM test and lab-based spirometry from moderate (Esco et al., 2011) to high (Väinämo et al., 1996; Peltola et al., 2000). In summary, the HRM method offers a simple, nonfatiguing way to assess aerobic capacity in young elite basketball players. However, since we did not compare these methods to a gold standard, the obtained values should be regarded with caution.